2018
DOI: 10.3989/gya.0346181
|View full text |Cite
|
Sign up to set email alerts
|

The impact of saturated monoacylglycerols on the oxidative stability of Canola oil under various time/temperature conditions

Abstract: Due to the inconsistency of monoacylglycerols’ (MAGs) impacts and the lack of research concerning the weight of saturated monoacylglycerols on the oxidative stability of oils, the current study was designed. For this purpose, saturated MAGs at 0.5, 3.0 and 5.0% were added to canola oil and subsequently exposed to a Schaall oven test at 60 °C for 31 days (to assimilate moderate thermal conditions and a prolonged treatment time) and a Rancimat test at 110 °C (to assimilate extreme thermal conditions and shorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…The injection was carried out with a ratio of 1:100, and nitrogen was selected as the carrier gas. The temperatures of the oven, injector, and detector were 175, 250, and 255°C, respectively (Naderi et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection was carried out with a ratio of 1:100, and nitrogen was selected as the carrier gas. The temperatures of the oven, injector, and detector were 175, 250, and 255°C, respectively (Naderi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Since edible oils and fats are heat‐sensitive compounds and in most cases exposed to high temperatures (mostly more than 100°C), they should have an acceptable thermal and oxidative stability because high‐temperature processing of oils leads to adverse reactions such as hydrolysis, oxidation, or polymerization (Taghvaei, Jafari, Assadpoor, Nowrouzieh, & Alishah, ; Taghvaei, Jafari, Nowrouzieh, & Alishah, ). These adverse reactions are associated with the production of anti‐nutritional and toxic substances, which in turn can put the consumer's health at a serious risk (Naderi, Farmani, & Rashidi, ). Studies have also shown that early products of fat oxidation, such as fatty acid peroxides, can cause various diseases such as atherosclerosis, cancer, cardiac and cerebral ischemia, allergic diseases, and early aging (Rafiee, Jafari, Alami, & Khomeiri, ; Taghvaei & Jafari, ).…”
Section: Introductionmentioning
confidence: 99%
“…Schaal oven accelerated stability test was performed. For this test 50 mL of each sample twice in glass vessels of internal diameter 88 mm and height 18 mm was measured and subjected to test conditions: at moderate temperatures (63 ± 2 °C), in the presence of air, without the presence of light according to the methodology described by Gomes et al (2010), Maszewska et al (2018), andNaderi et al (2018) for a period of 4 and 8 days. In the initial samples (0 th day of the test), 4 th , and 8 th day of the test peroxide value, PV, p-anisidine value, p-AnV, total oxidation value, TOTOX, conjugated dienes, CD, and conjugated trienes content, CT, were investigated.…”
Section: Accelerated Stability Testsmentioning
confidence: 99%
“…Next, the prepared oleogels were stirred at 200 rpm for 10 minutes. Finally, SMS/STS-based fats were cooled up to 20°C and kept for later analysis (Naderi et al, 2018).…”
Section: Preparation Of Oleogelsmentioning
confidence: 99%
“…The carrier gas was nitrogen and a ratio of 1:100 was selected for injection. The temperatures of the detector, injector and oven were 220, 225, and 180°C, respectively (Naderi et al, 2018).…”
Section: Fatty Acids Compositionmentioning
confidence: 99%